Michel Foucault e a demarcação dos limites da verdade - Bezeruska, Jussara Tossin Martins (2009)
This work aims to study the foucaultian question about the truth and the delimitation of its frontiers. At first it addressed the problem of the meaning of Archaeology under the philosophy of Foucault. Are then exposed some considerations about its basic features and is examining the problem of its location between the theories and methodologies. Then, it addresses the points where the archeaology is different from the ideas and histories of science and it is a reflection on some of its central objectives. Finally, we describe, detail and place one of its main objects is the wording. In the following chapter is to analyze the most important points of the history of madness in order to understand, in midst of this work, the conceptual and methodological applications characterized by Foucault in Archaeology of knowledge. In a third time looks to the words and things and there is this work the study done by Foucault on the birth of human sciences. Studies are some examples used by the philosopher, emphasizing the points made about the configurations and characteristics of natural history - as representative of traditional knowledge - and biology - as representative of modern knowledge, with emphasis on the moment when the knowledge of natural history disappears giving rise to knowledge of biology. Aimed to make clearer the paths used by Foucault in his research that allowed the emergence of a new form of relationship with the truth, is to understand the options and the development of methodological concepts which frame the proposed approach to archaeological Foucault.